Performance Analysis of Fractional Order Band Pass Filter - Yokus, Yunus Emre; Ozakin, Aslihan; Ayten, Umut Engin (IEEE, 2023)
This work is aimed at generalizing the design of continuous-time second-order band pass filter in the fractional-order (FO) domain with different orders. FO band pass filter (FOBPF) design, realized through the substitution of FO capacitor (FOC) and FO inductor (FOI) by appropriate active emulators, are presented in this paper. The implementation of FOC/FOI emulators has been achieved using Current Feedback Operational Amplifiers (CFOAs) as an active element. Also, the realization of the required FO differentiation/integration, for emulating the FOC and FOI, is performed through the employment of an integer-order (IO) Follow-the-Leader Feedback (FLF) multi-feedback topology. An important benefit, from the design flexibility point of view, is that the same topology could be used for emulating both FOC and FOI, and this is achieved through an appropriate selection of the time-constants and gain factors. The behavior of the FOC/ FOI emulator and FOBPF has been studied through the LTspice simulator. In order to simulate the behavior of FOC/FOI emulators, the AD844 discrete IC component model, which is available on the market as CFOA was used.
Keywords: fractional-order circuits; fractional-order elements; fractional-order filters; Computer Science; Communication; Engineering; Telecommunications